Amycolatopsis panacis sp. nov., isolated from Panax notoginseng rhizospheric soil. Issue 2 (3rd January 2019) - Peng, Guang; Xiong, Deng-Sen; Li, Lin-Chao; Hu, Jia-Yun; Bao, Sheng; Chen, You-Wei; Li, Yi-Qing; Xu, Li-Hua; Miao, Cui-Ping; Zhao, Li-Xing
Abstract : A novel Gram-positive bacterium, designated strain YIM PH21725 T, was isolated from a sample of rhizospheric soil of Panaxnotoginseng cultivated in Anning, Yunnan. The strain contained meso -diaminopimelic acid in the cell-wall peptidoglycan. The main fatty acids identified were C17 : 0, iso-C15 : 0, iso-C16 : 0 and C16 : 0 . The main menaquinone was MK-9 (H4 ). The polar lipids included phosphatidylethanolamine, diphosphatidylglycerol, phosphatidylinositol mannoside, phosphatidylinositol, phospholipids and phospholipids of an unidentified structure containing glucosamine. The G+C content of genomic DNA was 69.43 mol%. On the basis of its 16S rRNA gene sequence, strain YIM PH21725 T should belong to the genus Amycolatopsis, and was closely related to Amycolatopsis sulphurea DSM 46092 T (98.57 %), Amycolatopsis jejuensis JCM13280 T (97.27 %), Amycolatopsis jiangsuensis KCTC 19885 T (96.88 %) and Amycolatopsis ultiminotia JCM 16989 T (96.8 %). The phenotypic, chemotaxonomic, phylogenetic and digital DNA–DNA hybridization results clearly indicated that strain YIM PH21725 T represents a novel species of the genus Amycolatopsis, for which the name Amycolatopsis panacis sp. nov. is proposed. The type strain is YIM PH21725 T (=CCTCC AA 2017044 T =KCTC 49031 T =DSM 105902 T ).